Model-Model Pembelajaran Pendidikan Matematika Pada Kurikulum Merdeka - Ramayenni Pane (LPPM Politeknik Pratama, 2023)
The Merdeka curriculum was introduced in response to global changes and increasingly complex educational needs, giving schools the freedom to design their own curriculum. In this context, the mathematics learning models used in schools become highly relevant. These models should not only be in line with the vision and mission of the school, but should also promote deep understanding and strong mathematical skills The research method used in this study is a literature study. This literature study involves collecting data from various literature sources, reading, recording, and managing research data with an objective, systematic, analytical, and critical approach. The focus of the research is on Mathematics Education Learning Models in the Merdeka Curriculum. The data analysis technique used in this research is content analysis. The Merdeka Curriculum has opened the door for the development of more innovative and relevant learning models in mathematics education. By adopting models such as contextual, cooperative, inquiry, technology-based, and project-based learning, mathematics teachers can help students develop a deep understanding of mathematics, critical thinking skills, and a high interest in this subject. Through joint efforts between teachers, schools, and the government, Indonesia can continue to improve the quality of mathematics education and produce a generation that is ready to face mathematical challenges in the modern era In the context of the Merdeka Curriculum, mathematics learning models are an important tool in building higher quality and relevant mathematics education. Through the use of models such as contextual, cooperative, inquiry, technology-based, and project-based learning, mathematics teachers can provide more interesting and meaningful learning experiences for students. This helps students develop a deep understanding of mathematics, critical thinking skills, and a high interest in the subject.